Electron-positron pair-production and neutrino energy-loss from the instability regions of very massive stars / Lurwan Garba Gaya - Lurwan , Garba Gaya (2019)
Understanding the end fates of very-massive stars has been very exciting and essential in Astrophysics. Electron-positron pairs and neutrinos are very critical on this important astrophysical process. Neutrinos are produced in large numbers from exploding massive stars and are extremely important probes of processes involve in supernovae before its explosion. In spite of tremendous developments recorded in recent times, state-of-the-art stellar evolution models would provide many information about instability of very-massive stars arising from eminent production of electron-positron pairs. The ambient photons in the interior of very-massive stars are sufficiently energetic to create electron-positron pairs just before ignition of any element heavier than oxygen during evolution of the stars. Realising importance of pair-production and neutrino energy-loss in determining end fates of very-massive stars, this work investigate adiabatic effects of pair-production on dynamical instability of very-massive stars with carbon-oxygen cores, within the range of 60 M⊙< MCO < 133 M⊙. Thermal energy, pressure, and entropy of pair-production from instability regions of these stars are also evaluated. Models with rotation in Small Magellanic Cloud (SMC) as well as those with and without rotation in Large Magellanic Cloud (LMC) are considered. Similarly, pair-neutrino emission which is the dominant cooling process in the instability regions of these stars is computed. On the other hand, the neutrino energy-loss through thermal processes is calculated from stellar models of 120, 150, 200, 300, 500 M⊙, with rotation and 120, 150 and 500 M⊙ without rotation at LMC with metallicity